TEACHING PROFILE OF MATHEMATICS TEACHERS ON CLASSROOM MANAGEMENT: A STUDY ON QUADRATIC EQUATIONS - Febriani, Amida Syifa; Bernadine, Nufe Auliya’; Friyana, Salsabila Bunga Eka; Rofiki, Imam (Journal of Authentic Research on Mathematics Education (JARME), 2024)
Classroom management is a crucial skill for teachers to enhance the quality of student learning. Previous research indicates that teachers often struggle with effective classroom management, leading to suboptimal learning outcomes. This study aims to describe the teaching profile of mathematics teachers in managing classrooms while teaching quadratic equations and to provide guidelines for teachers to design instructional models that motivate and engage students. This descriptive research employs a qualitative approach. Data collection techniques include observations, interviews, and documentation. Data analysis involves data collection, condensation, presentation, and conclusion drawing. The results indicate that teachers have successfully implemented student-centered learning and managed classrooms effectively. Teachers were able to motivate students, increase their enthusiasm, and pose thought-provoking questions that had a positive impact. These findings contribute to the understanding of effective mathematics classroom management and provide guidance for mathematics educators in adopting student-centered approaches.